1(y)=1(-4x-6)

Simple and best practice solution for 1(y)=1(-4x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1(y)=1(-4x-6) equation:


Simplifying
1(y) = 1(-4x + -6)

Reorder the terms:
1y = 1(-6 + -4x)
1y = (-6 * 1 + -4x * 1)
1y = (-6 + -4x)

Solving
1y = -6 + -4x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '1'.
y = -6 + -4x

Simplifying
y = -6 + -4x

See similar equations:

| 5d-4=4 | | x-3/3=4+x/4 | | 3(2x+5)=2(4x+5)+9 | | 5d-4= | | Y=x/3+12 | | 6x-5=-53 | | 1.1q-1.9-2.4q=-2.3q-3.4 | | x-3x+5x=1 | | 2/5+3x=-118/5 | | -1=x/7+1 | | 0.55x+0.05(18+x)=0.10(-41) | | -1(y)=-1(-4x-5) | | (3+2i)+(5-2i)=8 | | -(6x+8)+12=3x-20 | | 563=a-334 | | 1(y)=1(-4x+2) | | -4x+1=-7/5 | | 3((16)1/2) | | 80+6a=7a-145 | | X+47=183 | | 180.75=40+5*x | | (2x-1)*6=(4-x)*3 | | 157=x-987 | | -5(3x+5)-3=-5(x+3)+2x | | 7((16)-1/2) | | x+2(x+1)=24+(x+4) | | 4x+3x+2=9 | | 15x-6=40x+9 | | 1/2n+2.5=18 | | 2x^2-51=0 | | (25x^2-10x-3)=0 | | 6.16=x-7z |

Equations solver categories